Nutritional support in the tertiary care of patients affected by chronic renal insufficiency: report of a step-wise, personalized, pragmatic approach. Issue 1 (December 2016) - Cupisti, Adamasco; D'Alessandro, Claudia; Di Iorio, Biagio; Bottai, Anna; Zullo, Claudia; Giannese, Domenico; Barsotti, Massimiliano; Egidi, Maria
Abstract Background Dietary treatment is helpful in CKD patients, but nutritional interventions are scarcely implemented. The main concern of the renal diets is its feasibility with regards to daily clinical practice especially in the elderly and co-morbid patients. This study aimed to evaluate the effects of a pragmatic, step-wise, personalized nutritional support in the management of CKD patients on tertiary care. Methods This is a case-control study. It included 823 prevalent out-patients affected by CKD stage 3b to 5 not-in-dialysis, followed by tertiary care in nephrology clinics; 305 patients (190 males, aged 70 ± 12 years) received nutritional support (nutritional treatment Group, NTG); 518 patients (281 males, aged 73 ± 13 years) who did not receive any dietary therapy, formed the control group (CG). In the NTG patients the dietary interventions were assigned in order to prevent or correct abnormalities and to maintain a good nutritional status. They included manipulation of sodium, phosphate, energy and protein dietary intakes while paying special attention to each patient's dietary habits. Results Phosphate and BUN levels were lower in the NTG than in the CG, especially in stage 4 and 5. The prevalence of hyperphosphatemia was lower in the NTG than in CG in stage 5 (13.3 % vs 53.3 %, p  < 001, respectively), in stage 4 (4.1 % vs 18.3 % vs, p  < 0.001) and stage 3b (2.8 % vs 9.5 %p  < 0.05). Serum albumin was higher in NTG than in CG especially in stage 5 . The use of calcium-free intestinal phosphate binders was significantly lower in NTG than in CG (11 % vs 19 %p  < 0.01), as well as that of Erythropoiesis stimulating agents (11 % vs 19 %, p  < 0.01), and active Vitamin D preparations (13 % vs 21 %, p  < 0.01). Conclusions This case-control study shows the usefulness of a nutritional support in addition to the pharmacological good practice in CKD patients on tertiary care. Lower phosphate and BUN levels are obtained together with maintenance of serum albumin levels. In addition, a lower need of erythropoiesis stimulating agents, phosphate binders and active Vitamin D preparations was detected in NTG. This study suggests that a nutritional support may be useful in the management of the world-wide growing CKD burden.